2020
DOI: 10.1177/1178221820918885
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Interventions for Patients in Opioid Maintenance Treatment: A Systematic Review

Abstract: Background: Opioid maintenance treatment (OMT) is the standard for treatment of opioid use disorder, but some individuals on OMT experience disrupted sleep, heightened sensitivity to pain, and continued relapse to non-medical opioid use. An adjunctive treatment that has potential to address these shortcomings of OMT is aerobic exercise. Objective: The aim of the present review was to identify and evaluate components of aerobic exercise interventions targeting OMT patients. Methods: For this PROSPERO-registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…We find a wide range of different outcomes in the included studies, which was also noted in another systematic review on the OST population. 33 As such, there is a need to coordinate a standard in physical function testing, which can increase the use of exercise tests in both research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We find a wide range of different outcomes in the included studies, which was also noted in another systematic review on the OST population. 33 As such, there is a need to coordinate a standard in physical function testing, which can increase the use of exercise tests in both research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, we explicitly focus on studies on PA in the treatment of OUD, that is, treatment for people with opioid dependence, such as heroin or prescription opioids. Although some previous systematic reviews 26 , 33 , 34 that cover OST have been published, these have included interventional studies exclusively, resulting in few studies. They showed that exercise interventions have the potential to improve health and wellness features for people in OST.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the challenges that SUD patients face, when pain is involved opioids are used as the first line of treatment without consideration of the after-effects. [12] An increase in evidenced based research is needed to strengthen the NP and all other providers' awareness of how to safely and effectively treat the SUD patient. [24] Two different substance use disorders were assessed in this review: alcohol and opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Over the past few decades, the liberal use of opioids to help relieve chronic pain has led to other undesirable effects such as addiction, morbidity and mortality. [11,12] Individuals who have a history of SUD are met with unique challenges when dealing with chronic pain. First, pain can present more intensely in individuals with SUD.…”
Section: Introductionmentioning
confidence: 99%